2016
DOI: 10.11648/j.ajce.20160405.11
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as a Drinking Water Treatment Coagulant

Abstract: Abstract:Inorganic aluminum or iron salts have been used for many decades to coagulate colloidal particles in surface water prior to flocculation, sedimentation and/or filtration. Although effective, inorganic coagulants have several disadvantages including large chemical dosages required for treating eutrophic waters, large volumes of chemical sludge produced, and toxic effects of metallic coagulants on the aquatic environment. Chitosan is a natural cellulose-like copolymer of glucosamine and N-acetyl-glucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…However, similarly to starch, it is insoluble in water, and it must be modified to increase its applicability and flocculating activity. There are only a few reports [ 5 , 88 , 89 ] with the use of this polymer in its unmodified form. Al-Manhel et al [ 89 ] studied application of chitosan dissolved in acetic acid in purification of water from the local river.…”
Section: Bio-based Polysaccharide Flocculants For Water Treatmentmentioning
confidence: 99%
“…However, similarly to starch, it is insoluble in water, and it must be modified to increase its applicability and flocculating activity. There are only a few reports [ 5 , 88 , 89 ] with the use of this polymer in its unmodified form. Al-Manhel et al [ 89 ] studied application of chitosan dissolved in acetic acid in purification of water from the local river.…”
Section: Bio-based Polysaccharide Flocculants For Water Treatmentmentioning
confidence: 99%
“…It has been identified that the MO seed extract contain cationic protein of polymerization which help in the low cost clarification procedures, has been widely used in the rural community areas to clear the cloudy water (Debora et al 2013;Marañón et al 2010). Another example, a natural polyelectrolyte of chitosan also has drawn much attention due to its high molecular weight and charged density along with its biodegradable polymer origin (Mohammadi et al 2014;Pontius 2016;Zonoozi et al 2011). Chitosan that is derived from deacetylation of chitin, are extensively found on natural sources and marine creatures such as arthropods, insects, crustaceans and fungi (Chi & Cheng 2006;Vieira et al 2012;Zonoozi et al 2011) while being the second most abundant biopolymer on Earth after cellulose (Jadhav & Mahajan 2013).…”
Section: Chemical and Natural Coagulantsmentioning
confidence: 99%
“…Among them includes limited availability in certain regions; it is not biodegradable; large chemical doses are necessary for the treatment of eutrophic waters, and a massive amount of chemical sludge is produced. 79,98,[112][113][114] Also, its residues cause harmful effects for both animal species [115][116][117] and public health. 115,[118][119][120][121] Hereupon, the total or partial replacement of the traditionally used compounds, with natural and biodegradable natural substances, is a solution that is being much discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%